Contributory Pensions Scheme and Workers’ Productivity in University of Port Harcourt - Orlu Chukwuemeka (International Journal on Economics, Finance and Sustainable Development, 2022)
The study examined contributory pension schemes and workers’ productivity in the University of Port Harcourt. The study was guided by three research questions. Relevant literature on the major variable under investigation was excavated. The paper was anchored on a life cycle theory. A descriptive research design was adopted for the study. Data were gathered through secondary and primary sources. The secondary data were sourced from textbooks, journal publications, newspaper publications, and university bulletins. The primary data were gotten from the researcher's personal observations and a self-made questionnaire structured on a four likert scale. Simple random sampling was used in the selection of a manageable sample size and the distribution of the researcher’s instrument to the respondents. The retrieved questionnaires were subjected to statistical analysis through the use of means and standard deviations. The criterion mean for decision making was at 2.5. That is, any mean above 2.5 is accepted while the alternative is rejected. The paper revealed that low coverage of the scheme, inadequacy of benefits from the pension scheme, poor awareness of contributory pension schemes, poor outreach of the management of pension schemes and non-compliance by the government are the major challenges bequeathing the contributory pension scheme at the Federal University of Port Harcourt.